Unraveling Assemblage, Functions and Stability of the Gut Microbiota of Blattella germanica by Antibiotic Treatment - Domínguez-Santos, Rebeca; Pérez-Cobas, Ana Elena; Artacho, Alejandro; Castro, José A.; Talón, Irene; Moya, Andrés; García-Ferris, Carlos; Latorre, Amparo (Frontiers in Microbiology, 2020)
Symbiosis between prokaryotes and eukaryotes is a widespread phenomenon that has contributed to the evolution of eukaryotes. In cockroaches, two types of symbionts coexist: an endosymbiont in the fat body (Blattabacterium), and a rich gut microbiota. The transmission mode of Blattabacterium is vertical, while the gut microbiota of a new generation is mainly formed by bacterial species present in feces. We have carried out a metagenomic analysis of Blattella germanica populations, treated and non-treated with two antibiotics (vancomycin and ampicillin) over two generations to (1) determine the core of bacterial communities and potential functions of the gut microbiota and (2) to gain insights into the mechanisms of resistance and resilience of the gut microbiota. Our results indicate that the composition and functions of the bacteria were affected by treatment, more severely in the case of vancomycin. Further results demonstrated that in an untreated second-generation population that comes from antibiotic-treated first-generation, the microbiota is not yet stabilized at nymphal stages but can fully recover in adults when feces of a control population were added to the diet. This signifies the existence of a stable core in either composition and functions in lab-reared populations. The high microbiota diversity as well as the observed functional redundancy point towards the microbiota of cockroach hindguts as a robust ecosystem that can recover from perturbations, with recovery being faster when feces are added to the diet.